Estudio de prefactibilidad para la instalación de una planta generadora de energía geotérmica - Diaz Chalco, Andres Gabriel (2023)
In recent years, uncontrolled urban growth has generated a series of concerns, one of which is the scarcity of sustainable electricity generation in Peru to maintain this pace. This concern forces us to look for new clean production alternatives to meet the growing demand for electricity. This research work supports geothermal energy as a key technology to achieve a reliable energy transition in Peru. The pre-feasibility study for the installation of a geothermal power plant located in the northern part of the department of Tacna allows us to evaluate the technical, economic, financial, environmental, social and market feasibility of this alternative and renewable means of electricity generation. The project shows us the problems in the southern macro region of the country, which has the largest energy deficit, because its consumption far exceeds local electricity production. Thanks to the market study, the target market for the proposed geothermal plant is identified. The main factors for determining the location of the plant are then identified. Subsequently, the types of plant size are analyzed, and the limitation corresponds to the technology size with an installed power capacity of 10 MW is determined. Then, the production processes, the selection of machinery and equipment, the dimensions of the facilities, the number of personnel and the maintenance system are defined. In addition, the economic and financial evaluation is developed to determine the feasibility of the research project whose required investment amounts to $ 48 219 759.24 USD.